THE EXISTENCE OF TIKTOKSHOP FOR MSMEs (From Opportunities to Challenges) - Jenny Nancy Kaligis; Umar Sako Baderan; Chevy Herly Sumerli A; Ainil Mardiah; Tono Mahmudin (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract The Tiktok Shop problem is getting hotter day by day. One side believes that Tiktok Shop can be a vehicle for MSMEs to expand their network and increase their market share. However, on the other hand, Tiktok Shop is actually considered a threat and challenge for MSMEs to develop their business because Tiktok Shop is different from other e-commerce, especially regarding the presence of foreign products, procedures that are not carried out well, and it is suspected that Tiktok also acts as a seller so that Tiktok Shop is too overpowered and has a big potential to kill MSME businesses. Moreover, MSMEs are the cornerstone of the Indonesian economy. Therefore, this research aims to analyze the existence of the Tiktok Shop for MSMEs, whether it is an opportunity or a threat. This research is qualitative research with a descriptive approach. This research uses secondary data obtained by researchers from scientific journals, books, credible websites and other reliable sources. The analysis technique in this research uses observation analysis techniques, data collection, data selection, data reduction, and drawing conclusions. The results of this research show that the existence of Tiktpk Shop for MSMEs is more of a threat than an opportunity. Keywords : Tiktok Shop, MSMEs, Challenges, Oportunity.